Development of a process and procedure for welding repair of HY-80 steel - Rosario Francia, Samuel (1999)
HY-80 steels; HY-130, such as HP9-4-20; 10Ni-Cr-Mo-Co are the strongest of the special tenacity and highest creep resistance properties, which have been developed for use in critical hydrospace and aerospace applications. In HY-80 type steel, the alloying elements that give high characteristics to the steels, in turn, increase the hardening power and therefore their tendency to crack. The relationship of the microstructure to the toughness property is evaluated for the welded metal and the region of the heat affected zone. SAW, SMAW or EBW welding processes are used in the manufacture of metal structures with these types of materials, however, in repairs or maintenance, the manual metal arc process with low hydrogen coated electrodes, with an adequate sequence and prior control to the qualification of the welder as well as the process in particular, allow presenting this work with satisfactory results.